2023
DOI: 10.1093/pnasnexus/pgad034
|View full text |Cite
|
Sign up to set email alerts
|

Crisscross multilayering of cell sheets

Abstract: Hydrostatic skeletons such as the Hydra’s consist of two stacked layers of muscle cells perpendicularly oriented. In vivo, these bilayers first assemble, and then the muscle fibers of both layers develop and organize with this crisscross orientation. In the present work, we identify an alternative mechanism of crisscross bilayering of myoblasts in vitro, which results from the prior local organization of these active cells in the initial monolayer. The myoblast sheet can be described as a contractile active ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
0
8
2
Order By: Relevance
“…This phenomenon may be due to the tendency of C2C12 cells to form multi-layered structures instead of monolayers as the confinement size decreases. 40,55 Incorporating compressive force exerted by surface-contracted cells into the theory of nematic elasticity remains a future challenge. Furthermore, we have demonstrated that the deformation of the cell nucleus was induced by establishing geometry-induced alignment of cells in the vicinity of tip regions where the cells undergo significant orientation change in the doublet and triplet circle boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be due to the tendency of C2C12 cells to form multi-layered structures instead of monolayers as the confinement size decreases. 40,55 Incorporating compressive force exerted by surface-contracted cells into the theory of nematic elasticity remains a future challenge. Furthermore, we have demonstrated that the deformation of the cell nucleus was induced by establishing geometry-induced alignment of cells in the vicinity of tip regions where the cells undergo significant orientation change in the doublet and triplet circle boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated the deformation of the cell nucleus also plays a role in controlling cell differentiation, such as mechanochemical signaling. 48 Because C2C12 cells fuse into myotubes through differentiation induction, 40,41,55 stretching of the nucleus under our designed geometric confinements could offer insights into the mechanism of force-induced morphogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 ] In vitro, it has recently been suggested that the geometry of the deposited ECM can determine the orientational field of a myoblast monolayer, creating zones of cell accumulation and multilayering. [ 33 ]…”
Section: Potential In Vivo Relevance Of the Patterns Of Constrained C...mentioning
confidence: 99%
“…To investigate whether CAFs exhibit nematic ordering similar to other elongated cells, such as myoblasts [24][25][26] , we seeded CAFs isolated from human colorectal tumors on 11 kPa polyacrylamide (PAA) gels coated with monomeric collagen I to maintain physiological substrate rigidity 27 . Over time, CAFs established a monolayer, comprising large regions of aligned cells forming nematic order (Fig.…”
Section: Cafs In Conjunction With the Fibronectin Matrix They Produce...mentioning
confidence: 99%